Trachelostenini sensu novo: redescriptions of Trachelostenus Solier, Myrmecodema Gebien and Leaus Matthews & Lawrence, based on adults and larvae, and descriptions of three new species of Leaus (Coleoptera: Tenebrionidae) - Matthews, Eric G.; Lawrence, John F. (Zootaxa, 2015)
The former family Trachelostenidae is returned to tribal status in Tenebrionidae-Tenebrioninae and reconstituted to include Trachelostenus Solier, 1851 of southern Chile, currently in a separate family Trachelostenidae, Myrmecodema Gebien, 1943 of central Chile, currently in Stenochiinae-Cnodalonini, and Leaus Matthews & Lawrence, 1992 of eastern Australia, currently in Tenebrioninae-Titaenini. The three genera are redescribed in both the adult and larval stages. Three new species: Leaus tropicalis sp.n. L. monteithi sp. n. and L. elusus sp. n. are described. Trachelostenine larval characters are compared with those of related tribes of Tenebrioninae: Titaenini, Heleini, Helopini, Helopinini, Ulomini and Toxicini. The Chilean genus Homocyrtus Dejean is briefly discussed and left incertae sedis in Tenebrionidae. Examination of Lagriola Kirsch (Lagriinae), originally associated with Trachelostenus, leads to the following name changes: Lagriola Kirsch, 1873 = Paratenetus Spinola, 1844, syn. n.; Paratenetus operosus (Kirsch, 1873) (Lagriola), comb. n.; Paratenetus championi, nom. n. for P. denticulatus Champion, 1886 nec P. denticulatus (Kirsch, 1873) (Lagriola) comb. n.